High color-stability for white organic light emitting devices by using phosphorescent sensitizer fluorescent - Juang, Fuh-Shyang; Hong, Lin-Ann; Hsiao, Chih-Jen; Wang, Shun-Hsi; Ho, Meng-Huan; Chen, Chin-Hsin (My University, 2010)
High color-stability white OLEDs can be achieved by replacing red fluorescent dopant (DCJTB) with yellow dopant (EY-53) in phosphor-sensitized emitter and optimizing the interlayer (CBP) thickness. Device shows the E.Q.E. of 8.2%, the efficiencies of 21.5 cd/A and 8.1 lm/VV with CIE (0.40, 0.46) at 20 mA/cm(2). The shift of ClExy down to (-0.001,-0.001) at a current density of 20 and 200 mA/cm2.